DORIVOR O‘SIMLIKLARINING ETIMOLOGIYASI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article provides information about the etymology of some medicinal plants.
Keywords: medicinal, medicine, flora, mountain region, pharmacognosy.